Willingness To Pay (WTP) Analysis for the Development of Pancor Kopong Water Tourism Facilities - M. Zainurrahman; Diswandi Diswandi; Muhammad Dzul Fadli (Indonesian Development Economics and Localities, 2025)
Pancor Kopong Water Tourism Object has a natural attraction in the form of a bathing pool surrounded by rice fields, with great potential for development. This study aims to analyze the magnitude of visitors' Willingness to Pay (WTP) towards the development of tourism facilities using a quantitative approach with a descriptive survey method. A sample of 99 respondents aged 16–35 years was selected purposively. The analysis techniques used include classical assumption tests, descriptive analysis, the Contingent Valuation Method (CVM), and multiple linear regression. The results showed an average WTP value of IDR 2,444, with a total estimated annual contribution reaching IDR 48,097,920. Of the five variables analyzed (age, gender, education, income, and duration of visit), only income had a significant effect on WTP. This finding confirms that economic factors are the main determinant of visitors' willingness to pay. This study recommends the need for participation-based tourism development and further studies with a wider range of locations and variables.